2022
DOI: 10.1101/2022.01.27.477980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular mechanisms of Plasmodium development in male and female Anopheles mosquitoes

Abstract: Vector competence influences the ability of Anopheles mosquitoes to transmit Plasmodium parasites. The aim of this study was to determine the competence of male and female Anopheles mosquitoes to support the development of Plasmodium parasites. Male and female A. stephensi (STE2 strain) were infected with in vitro-cultured P. berghei (ANKA strain) ookinetes. We found that the number of oocysts produced was higher in males than in females. RNA-seq analysis of male and female mosquitoes injected with P. berghei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Furthermore, Saglin is not secreted at detectable levels in the hemolymph where it could potentially serve as a chemotactic attractant for sporozoites. In addition, a recent study has shown that sporozoites do invade the salivary glands of male Anopheles mosquitoes [43] although saglin expression is female-specific [18,19]. Taken together, these observations indicate that Saglin is unlikely to be a determinant for sporozoite invasion of the salivary glands as sporozoites should not come in contact with this protein before reaching the lumen of salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Saglin is not secreted at detectable levels in the hemolymph where it could potentially serve as a chemotactic attractant for sporozoites. In addition, a recent study has shown that sporozoites do invade the salivary glands of male Anopheles mosquitoes [43] although saglin expression is female-specific [18,19]. Taken together, these observations indicate that Saglin is unlikely to be a determinant for sporozoite invasion of the salivary glands as sporozoites should not come in contact with this protein before reaching the lumen of salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…Classical fundamental studies have identified the midgut of vectors as the main arena for development of ookinetes and oocysts of hemosporidian parasites (Valkiunas, 2004;Hajkazemian et al, 2021). Few additional studies suggest that development of oocysts is possible also in posterior parts of the dipteran digestive tract, such as the hindgut and the rectum, however without indications of completion of this development or effects on the number of produced sporozoites (Haraguchi et al, 2022). We find that the sections of the hippoboscid digestive tract after the midgut appear to contain more parasites than the midgut itself.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the hypothesis that Saglin may not contribute to salivary gland invasion by sporozoites. A recent study has shown that sporozoites do invade the salivary glands of male Anopheles mosquitoes (Haraguchi et al ., 2022) while saglin is female-specific (Arcà et al ., 2005; Klug et al ., 2021). Taken together, these observations indicate that Saglin is unlikely to be a determinant for sporozoite invasion as sporozoites should not come in contact with this protein before reaching the luminal side of salivary glands.…”
Section: Discussionmentioning
confidence: 99%